2004
DOI: 10.1038/sj.cr.7290241
|View full text |Cite
|
Sign up to set email alerts
|

Soluble expression and characterization of a GFP-fused pea actin isoform (PEAc1)

Abstract: A pea actin isoform PEAc1 with green fluorescent protein (GFP) fusion to its C-terminus and His-tag to its Nterminus, was expressed in prokaryotic cells in soluble form, and highly purified with Ni-Chelating Sepharose TM Fast Flow column. The purified fusion protein (PEAc1-GFP) efficiently inhibited DNase I activities before polymerization, and activated the myosin Mg-ATPase activities after polymerization. The PEAc1-GFP also polymerized into green fluorescent filamentous structures with a critical concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…However, there has been few reports of visualizing GFP-actin in plant cells, such as enrichment of actin-GFP around the nuclei and near the tip and cell wall in N . tabacum BY2 suspension cells 23 , and bundle-like patches of actin-GFP on mitochondria in N . tabacum protoplasts 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there has been few reports of visualizing GFP-actin in plant cells, such as enrichment of actin-GFP around the nuclei and near the tip and cell wall in N . tabacum BY2 suspension cells 23 , and bundle-like patches of actin-GFP on mitochondria in N . tabacum protoplasts 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies successfully visualized actin filaments in other live eukaryotic cells, including Dictyostelium discoideum 20 and mammalian cells 21 , 22 , by expression of GFP-actin. In plant cells, two studies reported expression of actin-GFP in Nicotiana tabacum BY2 cells and protoplasts, respectively, but no long filamentous structures were observed even though localized GFP fluorescence was detected 23 , 24 . For these reasons, GFP fused with the actin-binding domain (ABD) of mouse talin1 (GFP-mTalin1), was the first GFP-based probe to observe actin filaments in living plant cells 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Although its use as an agent to facilitate the soluble expression of proteins that misfold or aggregate when overproduced in Escherichia coli has been approached with caution [85], success has been reported for a plant actin [86]. We reasoned that, given its robust solubility, it might be used to facilitate soluble expression of the intractably insoluble IS 2 TPase under native conditions.…”
Section: Discussionmentioning
confidence: 99%
“…PCR ampliWcations were performed on 1-l cDNA template using the kit PCR Master (Roche). The sequences of the primers used for PCR ampliWcations were the following ones: for PsMPK2 (AF154329), forward 5Ј-GGATCCAT GGCGACTCCGGTCGAGCC-3Јand reverse 5Ј-CAGAAT ATATATCGAGCTCACCGATGACCG-3Ј corresponding with the 3Ј UTR; for the actin PEAct1 (X67666) (Liu et al 2004), forward 5Ј-GGATCCAAAAGATGGCCGATGCT GAGGAT-3Ј and reverse 5Ј-GCAAAATCACTTACCATT ATACGCGC-3Ј.…”
Section: Rt-pcrmentioning
confidence: 99%